Analysis of the Multiple Drug Resistance (MDR) Pattern Among Uropathogenic Klebsiella Pneumoniae Isolates from Immunocompromised Patients - Alaa Abd Atia; Manal Mohammed Kadhim (Academia Open, 2025)
Background: Multidrug-resistant (MDR) Klebsiella pneumoniae is a major causative agent of urinary tract infections (UTIs) and represents a growing therapeutic challenge, particularly in immunocompromised patients. The purpose of this study was to determine the prevalence of MDR in K. pneumoniae isolates from immunocompromised patients with UTIs. Methods: Urine samples were collected from 597 immunocompromised patients with UTIs. K. pneumoniae was isolated and identified, and the isolates were subjected to susceptibility testing against 25 antibiotics. Results: Fifty-two (12.2%) K. pneumoniae isolates were isolated from 427 positive urine samples. The results showed a high prevalence of MDR (73.1%) with specific resistance patterns associated with certain antibiotic classes. The relationship between MDR and patient demographic and clinical variables was also analyzed, and statistically significant associations were found between the presence of the pattern and length of hospital stay (P=0.0238), prolonged infection duration (P=0.0026), use of indwelling urinary catheter (P= 0.0014), and history of antibiotic treatment (P = 0.0019). Conclusion: The prevalence of MDR K. pneumoniae was higher in immunocompromised patients, and its occurrence was associated with a longer length of stay, prolonged infection, catheter use, and a history of antibiotic treatment. Highlights: 73.1% of K. pneumoniae isolates were multidrug-resistant. MDR linked to longer hospital stays, catheter use, and prior antibiotics. Serious concern for treating UTIs in vulnerable patients. Keywords: Multidrug Resistance, Klebsiella Pneumoniae, Urinary Tract Infection, Immunocompromised Patients, Antibiotic Resistance